On characterizations of curves in the galilean plane - Yüzbaşı, Zühal Küçükarslan (Palestine Polytechnic University, 2020)
In this paper, we study Smarandache curves and curves of constant breadth by using the Galilean plane frame in G2. Moreover, we get some characterizations of these types of special curves in G2. © Palestine Polytechnic University-PPU 2020.
Keywords: Curves of constant breadth; Galilean plane; Smarandache curves